MITIGASI BENCANA BERBASIS MASYARAKAT PADA DAERAH RAWAN LONGSOR DI DESA KALITLAGA KECAMATAN PAGETAN KABUPATEN BANJARNEGARA JAWA TENGAH - Parlindungan R., Ranto; Fathani, Teuku Faisal; Karnawati, Dwikorita (Civil Engineering Forum Teknik Sipil, 2008)
This research was carried out due to the occurrence of mass movement in Kalitlaga Village Pagentan Sub-District Banjarnegara District, which was one of most dangerous area to mass movement in Province Central Java. Such movement resulted in damaged houses and road. This research was conducted to recognize and identify the direction and type of mass movement, to identify the triggering parameters and the cause of mass movement in order to provide an appropriate disaster mitigation recommendation and prevention method, as well as to introduce low cost early warning system based on community which enabled the community to prepare and operate the system in lessening the disaster risks. Secondary and primary data used in this research were derived from field investigation and study. The method of the study is analyzing the results of field study. To obtain the percentage of people understanding on disaster mitigation, landslide, and early warning system, interviews were conducted and the interviews outputs were processed using the SPSS software. Result shows that the landslide is predominantly northeastern ward and slump type of movement. To the number of leaky water pipe and infiltrations into the ground induce the mass movement. This movement is due to geological factors such as geomorphology factor and existence of clay stone as well as high rainfall factor. The community low understanding on disaster mitigation represents the reason to install simple and cheap early warning system community based disaster mitigation. Such mitigation is easier to apply than technology based mitigation. It is also more suitable prior to a disaster. Community participation and also support from government are the key efficacy of disaster mitigation.